Innovative technique of separating commingled thermoplastics to enhance materials recovery - 343382 Israil Ahmed (Skudai : Universiti Teknologi Malaysia, 1998)
Thesis (Master of Engineering (Chemical) - Universiti Teknologi Malaysia, 1998